Effect of interventions for non-emergent medical transportation: a systematic review and meta-analysis - Paul G. Shekelle; Meron M. Begashaw; Isomi M. Miake-Lye; Marika Booth; Bethany Myers; Andrew Renda (BMC Public Health, 2022)
Abstract Introduction Transportation is an important social determinant of health. We conducted a systematic review of the associations on health and health care utilization of interventions aimed at reducing barriers to non-emergency transportation and non-medical transportation. Methods We searched three databases and the gray literature through mid-January 2022. Included studies needed to assess an intervention targeted at non-emergency or non-medical transportation barriers, report missed (or kept) visits, health care utilization, costs, or health outcomes. Data extraction was performed in duplicate and included information about study design, results, and risk of bias. Primary outcomes were frequency of missed appointments, health care utilization, costs, and health outcomes. Synthesis was both narrative and meta-analytic using a random effects model. Results Twelve studies met inclusion criteria, three randomized trials, one controlled trial, and eight observational studies. All included studies had some element of risk of bias. Populations studied usually had chronic or serious health conditions or were poor. Interventions included van rides, bus or taxi vouchers, ride-sharing services, and others. Meta-analysis of seven studies (three trials, four observational studies) yielded a pooled estimate of missed appointments = 0.63 (95% confidence interval [CI] 0.48, 0.83) favoring interventions. Evidence on cost, utilization, and health outcomes were too sparse to support conclusions. Evidence on the effect of non-medical transportation is limited to a single study. Conclusions and relevance Interventions aimed at non-emergency transportation barriers to access health care are associated with fewer missed appointments; the association with costs, utilization or health outcomes is insufficiently studied to reach conclusions. This review was registered in PROSPERO as ID CRD42020201875.